2013
DOI: 10.1093/molehr/gat025
|View full text |Cite
|
Sign up to set email alerts
|

The source and significance of DNA damage in human spermatozoa; a commentary on diagnostic strategies and straw man fallacies

Abstract: This article considers the origins of DNA damage in human spermatozoa, the methods that are available to monitor this aspect of semen quality and the clinical significance of such measurements. DNA damage in spermatozoa appears to be largely oxidative in nature, inversely correlated with levels of nuclear protamination and frequently associated with the activation of a truncated apoptotic pathway. DNA base adducts formed as a result of oxidative attack are released from the spermatozoa into the extracellular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
1
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(110 citation statements)
references
References 87 publications
2
101
1
6
Order By: Relevance
“…Taking into consideration all these results, we can state that, although human sperm DNA is susceptible to damage as a result of bacterial semen infection, changes in lipid sperm membrane structures are critical for sperm fertilizing potential in this pathological condition. Moreover, this statement supports the general opinion postulated by some authors regarding the role of sperm DNA integrity as a predictor of the genetic quality of the embryo rather than of fertility [120,121]. However, further research is required in order to recommend the marker with the best prognostic power in clinical practice reflecting lipid sperm membrane damage during bacterial semen infection.…”
Section: Apoptosis/necrosissupporting
confidence: 84%
“…Taking into consideration all these results, we can state that, although human sperm DNA is susceptible to damage as a result of bacterial semen infection, changes in lipid sperm membrane structures are critical for sperm fertilizing potential in this pathological condition. Moreover, this statement supports the general opinion postulated by some authors regarding the role of sperm DNA integrity as a predictor of the genetic quality of the embryo rather than of fertility [120,121]. However, further research is required in order to recommend the marker with the best prognostic power in clinical practice reflecting lipid sperm membrane damage during bacterial semen infection.…”
Section: Apoptosis/necrosissupporting
confidence: 84%
“…[33] The TUNEL assay is also im- peded by the highly compacted nature of sperm chromatin and necessitate the introduction of a chromatin decondensation step, prior to commencement of the assay in order to avoid potential artefacts. [34] On the other hand, both the TUNEL assay and the SCD test have been reported to require higher levels of DNA and chromatin damage before they can detect structural changes, indicating that they have lower sensitivity than the SCSA and the comet assay. [35] In conclusion, as far as the comet assay can detect, high degrees of sperm DNA damage are accompanied by significant impairment in all seminal parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The principal cytotoxic reactive oxygen intermediate involved in ROS-associated damage is probably hydrogen peroxide (H2O2) generated by the intracellular dismutation of superoxide anion (O2-) under the influence of superoxide dismutase (SOD). However, Cameroun and Bernard (2007) suggested that the hydroxyl radical (HOO°), formed by the protonation of O2-, could be a potent indicator of per oxidative damaging human spermatozoa [2,52]. Though, in addition to H2O2, lipid peroxides generated as consequence of the peroxidation process also appeared to be profoundly cytotoxic, as their degradation products do.…”
Section: Discussionmentioning
confidence: 99%
“…Cell death can be developmentally controlled, with apoptosis being the most common morphologic expression of such programmed cell death [1][2][3][4]. Lethal cellular programs that lead to apoptosis may be triggered by a variety of exogenous and environmental stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation